Bioactivity of microencapsulated essentials oils on the ectoparasitic mite Varroa destructor (Acari: Varroidae) and perspectives of their use in the control of Varroosis - Ruffinengo, Sergio Roberto (2014)
Attractant/repellent and acaricidal effects of two microencapsulated essential oils, Acantholippia seriphioides (A. Gray) Mold. and Schinus molle L., were evaluated on the ectoparasitic mite Varroa destructor Anderson et Truemann using complete exposure and evaporation tests. Mites and honey bees (10 specimens of each per dish) were introduced in Petri dishes having different microencapsulated essential oil doses (0.25, 0.5 and 1 g). Mite and honey bee mortality were registered at 24, 48 and 72 hrs. An attractant/repellent test was performed using a device with two tubes of virgin wax closed on one side. Microencapsulated essential oils were placed at the end of one of the tubes. One mite was placed inside a tube with no oil and its position was observed after 90 min. Microencapsulated oils differed in the level of toxicity caused to V. destructor, A. seriphioides oil toxicity was higher than S. molle oil. Negative effects were registered on honey bees when they were completely exposed to microencapsulated oil of A. seriphioides. Microencapsulated oil of S. molle had attractant properties. None of the two microencapsulated oils tested had repellent effects on mites. This study might be a starting point for future researches of microencapsulated essential oils, as they offer a good alternative in the control of varroatosis.